The Complexity of Hate Crime and Bias Activity: Variation across Contexts and Types of Bias. (2nd January 2017) - Gladfelter, Andrew S.; Lantz, Brendan; Ruback, R. Barry
Abstract : Are racially-motivated hate crimes, non-criminal bias incidents, and general forms of crime associated with the same structural factors? If so, then social disorganization, a powerful structural correlate of general crime, should predict rates of hate incidents. However, tests of social disorganization's effects on racially-motivated hate crime yield inconsistent results. This study uses data from the Pennsylvania Human Relations Commission (PHRC) to explore such inconsistencies. Specifically, we assess the effects of social disorganization across contexts and types of bias motivation using bias incidents over 12 years. The results suggest that (a) social disorganization, particularly residential instability, is robustly correlated with rates of both hate crime and other prejudicial conduct, and that (b) the interactive effects of social disorganization help explain variations in incident rates by motivation type. Specifically, anti-black incidents are most frequent in unstable, homogeneous (i.e. white) and advantaged communities, while anti-white incidents are most frequent in unstable, disadvantaged communities.